Development of mathematical model of decision making based on analysis of values of stakeholders - Оберемок, Иван Иванович; Оберемок, Наталья Васильевна (Technology audit and production reserves, 2017)
The values are one of the key concepts used in modern project management methodologies. Decision-making in the project without the participation and attention to the values of stakeholders leads to a failure in the projects. The study describes the value of an interested party of the project as a set of indicators to assess its condition. The mathematical description of stakeholder relations to values is proposed. Based on the description of the relationship to the values, the objective function of maximizing the degree of security of the entire set of stakeholder values is proposed. Tangible and intangible assets owned or wanted to own by the interested party are presented as artifacts affecting the degree of security of stakeholder values. A formula is proposed for evaluating priority of artifacts resulting from stakeholder participation in projects. An approach to the assessment of the current degree of security stakeholder values is proposed. The mathematical description is proposed for the portfolio of projects and programs, which involved stakeholders in order to maximize the level of security of their valuables. A description of the project is made as a process of transformation of artifacts owned by the interested party in the artifacts that it would like to own. The target decision-making function is given to change the portfolio in order to obtain the maximum level to ensure stakeholder value. Recommendations for project leaders on the formation of values are given. Decomposing the project taking into account the priority of the artifacts, project manager provides the support of key stakeholders.